A VIEW AT THE TEACHING-LEARNING PROCESS IN THE WRITING OF TEXT IN THE INITIALS STAGES OF FUTURE ENGLISH PROFESSORS - Cabezas Santana, Eunises (Atenas, 2012)
The following article broaches important aspects related with the teaching-learning process of the texts written construction in the initial formation process of English language professors. The article goes into details related with the determination of the associated elements with the initial formation process of foreign languages speakers, as from the theoretical existent frame and his adjustment to the present-day transformations of the Cuban universities. In like manner, the development of the texts written construction in English language as a communicative ability is conditioned for the current interrelation among thought and language and the theoretical conception of the communicative approach focused in the consideration of the writing as a complex process of communication.